Open-plan office design for improved natural ventilation and reduced mixed mode supplementary loads - Abdullah, Hardi K.; Alibaba, Halil Z. (Sage Publications Ltd, 2022)
The hybrid philosophy behind the mixed-mode (MM) strategy aims at achieving energy-efficient buildings and sustainable development. A performance-based open-plan office design facilitates the handling of multiple design parameters to identify optimal design solutions for effective MM offices. This research presents a method of open-plan office design for an improved natural ventilation potential and reduced supplementary heating/cooling loads in the early design stage within a Mediterranean climate. Different design variables including office size, layout aspect ratio, window orientation and fraction of window opening, with several factor levels, were studied. The design of experiment developed by theTaguchimethod was applied to define the most informative simulation scenarios. Analysis of variance was utilised to indicate the effectiveness of each design parameter, while the signal-to-noise ratio approach identified the near-optimal level combinations that support informed decision-making. Suggested by the EN 15251:2007 standard, the hourly dynamic simulations were conducted using TAS Engineering. The measurement criteria included airflow rate, carbon dioxide (CO2) levels, adaptive thermal comfort and air-conditioning (AC) loads. The calculated indicator was the number of hours in which a specific performance criterion is met during the occupancy period and the AC loads.
Keywords: Open-plan office; Natural ventilation; Mixed-mode strategy; Adaptive comfort; Performance-based design; Taguchi method